Exam Ref 70-532 developing Microsoft Azure solutions - Tejada, Zoiner; Bustamante, Michele Leroux; Ellis, Ike (Microsoft Press, 2015)
Prepare for Microsoft Exam 70-532-and help demonstrate your real-world mastery of Microsoft Azure solution development. Designed for experienced developers ready to advance their status, Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the Microsoft Specialist level. Focus on the expertise measured by these objectives: Design and implement Websites Create and manage Virtual Machines Design and implement Cloud Services Design and implement a storage strategy Manage application and network services This Microsoft Exam Ref : Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Will be valuable for Microsoft Azure developers, solution architects, DevOps engineers, and QA engineers Assumes you have experience designing, programming, implementing, automating, and monitoring Microsoft Azure solutions and that you are proficient with tools, techniques, and approaches for building scalable, resilient solutions Developing Microsoft Azure Solutions About the Exam Exam 70-532 focuses on the skills and knowledge needed to develop Microsoft Azure solutions that include websites, virtual machines, cloud services, storage, application services, and network services. About Microsoft Certification Passing this exam earns you a Microsoft Specialist certification in Microsoft Azure, demonstrating your expertise with the Microsoft Azure enterprise-grade cloud platform. You can earn this certification by passing Exam 70-532, Developing Microsoft Azure Solutions; or Exam 70-533, Implementing Microsoft Azure Infrastructure Solutions; or Exam 70-534, Architecting Microsoft Azure Solutions. See full details at: microsoft.com/learning.
Includes index. - Online resource; title from title page (Safari, viewed March 11, 2015)
Keywords: Database management -- Study guides -- Examinations; Cloud computing -- Study guides -- Examinations; Computing platforms; Bases de données; Gestion; Examens; Guides de l'étudiant; Infonuagique; Examens; Guides de l'étudiant; Plateformes (Informatique); Database management; Examinations; Study guides